Sistem Blusukan Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Ahmad Gawdy Prananosa; Donni Pestalozi; Marianita Marianita; Rudi Erwandi; Nyayu Masnon; M. Rusni Eka Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT This study aimed to determine the school principal's Alaskan system in improving teacher performance. This study uses a qualitative approach with phenomenological methods. This research was conducted at elementary school principals in Lubuklinggau City. The subjects in this study were all people seen by researchers as able to provide data about the elementary school principal's Alaskan system in improving teacher performance. The research subjects included school principals, teacher boards, and staff. Data collection techniques include; observation, interview, and documentation. In contrast, the data analysis technique used is the data analysis method, according to Miles & Huberman, namely interactive model analysis. Data analysis took place simultaneously, which was carried out simultaneously with the data collection process with a flow of stages: data collection (data collection), data reduction (data reduction), data presentation (data display), and conclusions or verification (conclusion drawing & verifying). The study results show the Alaskan system for leaders in knowing the condition of their subordinates do not have to do blusukan every day because they remember that leaders must carry out other tasks in carrying out their duties. Blusukan can also be carried out suddenly to find out the condition of their subordinates at work, and then also, in the era of the advancement of information technology era leaders can utilize information technology tools to support the activities of carrying out blusukans such as the use of CCTV media to monitor the conditions of their subordinates at work. In conclusion, the school principal blusukan system can utilize information technology tools to support blusukan implementation activities, such as the use of CCTV media to monitor the conditions of his subordinates at work Keywords: System, blusukan, principal, performance, teacher